Towards the mainstream a case study on the budots dance craze - Flores, Fritz E.
A novel media studies research focused on Davaoeño pop culture, ?Towards the mainstream: A Case study on the Budots Dance Craze? explores and analyzes Budots, a local dancing style that gained immense mainstream popularity. On a wider scope, this research study also analyzes the extent of mass media's inlfuence in the formation of certain perceptions on concepts that exist in our society. For the data gathering process, the researcher conducted an exploratory study (which involved interviews and documentations) on urban depressed areas such as barangays Matina Aplaya and Leon Garcia in order to establish the ?image? of Budots (given that it was in these places where the dance really originated). The researcher also conducted visits and interviews with the staff and disc jockeys of ABS-CBN Davao. George Gerbner's Cultivation Theory was used as a framework in interpreting and analyzing the data acquired. The data acquired shows that mass media were able to perform the three B's of Gerbner's Cultivation Theory, in the context of mainstreaming Budots. First, it was able to ?blur? certain stereotypes, create a mainstreamed reality and ?blend? it to the realities of the audience and ?bend? this mainstreamed reality towards their advantage. Thus, it can be said that mass media's power in mediating the formation of the human's perception about certain phenomena and the society as a whole is very immense. It can be used as a tool to influence (or at some point manipulate) how humans understand and grasp certain concepts existing in our society.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media arts